2015
DOI: 10.1371/journal.pone.0122164
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Biodiversity and Setting Conservation Priorities for SE Queensland’s Rainforests Using DNA Barcoding

Abstract: Australian rainforests have been fragmented due to past climatic changes and more recently landscape change as a result of clearing for agriculture and urban spread. The subtropical rainforests of South Eastern Queensland are significantly more fragmented than the tropical World Heritage listed northern rainforests and are subject to much greater human population pressures. The Australian rainforest flora is relatively taxonomically rich at the family level, but less so at the species level. Current methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 90 publications
(182 reference statements)
3
60
0
1
Order By: Relevance
“…Graphical representation derived from the phylogenetic tree for SE Queensland based on three DNA barcode markers indicating by colored bars the species present in each of the subregions. (from Shapcott et al, ).…”
Section: Hotspots In the Application Of Plant Dna Barcodes Todaymentioning
confidence: 99%
See 2 more Smart Citations
“…Graphical representation derived from the phylogenetic tree for SE Queensland based on three DNA barcode markers indicating by colored bars the species present in each of the subregions. (from Shapcott et al, ).…”
Section: Hotspots In the Application Of Plant Dna Barcodes Todaymentioning
confidence: 99%
“…For the applied users of taxonomy, DNA barcoding serves as a means to identify regulated species, invasive species, and endangered species, and to test the identity and purity of botanical products, such as commercial herbal medicines and dietary supplements. DNA barcodes are now also being used to address ecological, evolutionary, and conservation issues, such as the ecological rules controlling the assembly of species in plant communities (e.g., Kress et al, ), the degree of ecological specialization found in plant‐animal networks (e.g., Jurado‐Rivera et al, ), and determining the most evolutionarily diverse habitats for protection (Shapcott et al, ).…”
Section: The Beginnings Of Plant Dna Barcodingmentioning
confidence: 99%
See 1 more Smart Citation
“…We froze each leaf or kernel subsample in liquid nitrogen and ground it to a powder using an MM2000 TissueLyser (Retsch, Haan, Germany) after adding disposable 0.1 and 2.3 mm diameter zirconia/silica beads (Daintree Scientific, St. Helens, Tasmania, Australia) [113]. DNA was extracted using a glass-fibre DNA-extraction protocol for plants [114].…”
Section: Paternity Analysismentioning
confidence: 99%
“…As an example, the use of PD has been shown to lead to greater preservation of 'feature diversity' in the Cape Floristic Region of South Africa (Forest et al, 2007). Phylogenetic techniques have also been employed to identify evolutionarily significant regions of diversity (Sechrest et al, 2002;Vandergast et al, 2008;Jetz et al, 2012;Kooyman et al, 2013;Mishler et al, 2014;Rosauer & Jetz, 2014;Laity et al, 2015;Nagalingum et al, 2015;Shapcott et al, 2015) and unique lineages (Isaac et al, 2007;Rosauer et al, 2009). As this approach gains popularity, the importance of testing the statistical significance of observed patterns has become paramount.…”
Section: Introductionmentioning
confidence: 99%